Temporal association between COVID-19 vaccination and Raynaud's phenomenon: A case series. Issue 1 (31st December 2023) - Lisy, Marcus; Urban, Nikolaus; Brunner-Ziegler, Sophie; Weber, Benedikt; Bauer, Wolfgang M.; Dassler, Eva; Koppensteiner, Renate; Handisurya, Alessandra
ABSTRACT: COVID-19 vaccine–related adverse events are mostly minor to moderate, and serious events are rare. Single cases of Raynaud's phenomenon (RP) in temporal proximity to COVID-19 vaccination have been reported. Demographic data, medical history, and detailed information regarding vaccination status and RP characteristics were obtained from patients with confirmed RP after COVID-19 vaccination. Fifteen participants reported the initial manifestation of RP, which occurred in 40% after the first, in 33% after the second, and in 27% after the third vaccination. RP development and occurrence of episodes were not linked to any specific vaccine type. New onset of disease was observed in 40% of the vaccinees after BNT162b2, in 33% after mRNA-1273, and in 27% after ChAdOx1 vaccination. Three out of four participants with preexisting RP prior to COVID-19 vaccination reported aggravation in frequency and intensity after immunization. Although COVID-19 vaccination is pivotal in controlling the pandemic, the observed temporal association between vaccine administration and RP occurrence warrants global activities to support pharmacovigilance for the detection of adverse reactions, one of which may include RP.